Establishment of a human pluripotent stem cell-derived MKX-td Tomato reporter system - Yuki Fujisawa; Lu Ming; Daisuke Yamada; Tomoka Takao; Takeshi Takarada (Stem Cell Research & Therapy, 2022)
Abstract Tendon regeneration is difficult because detailed knowledge about tendon progenitor cells (TPCs), which produce tenocytes to repair tendon tissue, has not been revealed. Mohawk homeobox (MKX) is a marker of TPCs or tenocytes, but a human pluripotent stem cell (hPSC)-based reporter system that visualizes MKX+ cells has not been developed. Here, we established an hPSC-derived MKX-tdTomato reporter cell line and tested the induction ratio of MKX-tdTomato+ cells using our stepwise/xeno-free differentiation protocol. MKX-tdTomato+ cells were generated with high efficiency and expressed tendon-specific markers, including MKX, SCX, TNMD, and COL1A1. Our MKX-tdTomato hPSC line would be a useful tool for studying the development or regeneration of tendon tissue.